2005
DOI: 10.1203/01.pdr.0000148714.51310.5e
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Pressure Autoregulation and Vasoreactivity in the Newborn Rat

Abstract: Perinatal brain injury has been associated with impaired cerebral blood flow (CBF) pressure autoregulation. The brain of 3-to 5-d-old rat pups is immature and similar to that of a preterm infant, and therefore we tested cerebral vasoreactivity in that animal. CBF pressure autoregulation was tested in 20 Wistar pups during normocapnia and hypercapnia, respectively. Hypotension was induced by hemorrhage and cerebral perfusion was monitored with laser Doppler flowmetry and near-infrared spectroscopy. Systolic blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…Clinical studies of neonates, which used the static autoregulatory index, have concluded that hypercapnia impairs autoregulatory reactivity in these patients (13,18). Finally, laboratory studies of acute hypercapnia in the newborn piglet and rat and the adult cat also have reported that hypercapnia impairs autoregulation (19,21,25). Our findings that induction of acute hypercapnia can impair autoregulation are consistent with these previously reported studies.…”
Section: Discussionsupporting
confidence: 91%
“…Clinical studies of neonates, which used the static autoregulatory index, have concluded that hypercapnia impairs autoregulatory reactivity in these patients (13,18). Finally, laboratory studies of acute hypercapnia in the newborn piglet and rat and the adult cat also have reported that hypercapnia impairs autoregulation (19,21,25). Our findings that induction of acute hypercapnia can impair autoregulation are consistent with these previously reported studies.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have also validated NIRSderived cerebral Hb signals during acute cerebral perfusion pressure manipulations with independent CBF measures such as CBF velocities (18,19), microspheres (20), or laser-Doppler flowmetry (21,22). All those studies support the hypothesis that Hb signals are reliable CBF surrogates during pressure maneuvers and may therefore allow assessment of dynamic AR.…”
Section: Discussionmentioning
confidence: 88%
“…First, we used the NIRS HbD signal as a surrogate for CBF. This was based on the strong correlation between HbD and CBF in previous animal validation studies (9,23). It may be argued that in some instances, a change in HbD could reflect a change in oxygen extraction fraction.…”
Section: Discussionmentioning
confidence: 99%